The Effects of Viewing Cute Pictures on Performance During a Basketball Free-Throw Task - Yoshikawa, Naoki; Masaki, Hiroaki (Frontiers in Psychology, 2021)
Previous studies have shown that viewing cute pictures leads to performance improvement in a subsequent fine motor task. We examined the beneficial effects of viewing cute pictures in a more complex sporting skill (i.e., basketball free throws) by comparing three conditions (viewing baby animal pictures, adult animal pictures, and no pictures) and two tests (no-pressure and pressure). The participants, all of whom were college basketball players, performed sixteen free throws in each condition. In the no-pressure test, male participants improved performance after viewing pictures of baby animals but not after adult animals and no pictures. In the pressure test, no significant improvement was observed. For female participants, the cuteness-viewing effect was not observed in both tests. The results suggest that viewing cute pictures may improve performance during basketball free throws in a low-pressure situation by narrowing the breadth of attentional focus and inducing approach motivation and caregiving behaviors.